Educational Institution-Building in Islam: Lessons for Pakistan - Rabia, Rabia; Aurangzeb, Aurangzeb; Fatima, Kulsoom; Raza, Muhammad Mustafa; Hamza, Muhammad (Journal Neosantara Hybrid Learning, 2024)
Institutions are the cornerstone of a state, ensuring its strength, stability, peace, and prosperity. Education, as a key institution, drives cognitive and socio-economic development. Islamic civilization emphasizes institution-building, providing a framework for establishing robust educational systems. This paper examines the Islamic concept of educational institution-building, focusing on inclusivity, equity, and quality education, and their role in shaping effective educational structures. The management of Islamic educational institutions is rooted in three principles: knowledge, upbringing, and arts. The Holy Prophet (Peace Be Upon Him) exemplified these principles, with the institution of Suffa serving as a prime example. This study explores the strategies of the Holy Prophet (Peace Be Upon Him) and examines their relevance to modern Pakistani educational institutions. Using a qualitative and exploratory approach, the research analyzes primary and secondary sources to study Islamic educational practices and their application in Pakistan. It identifies challenges in Pakistan's education system, such as inequity and quality deficits, and proposes strategies inspired by Islamic teachings to address these issues effectively. The findings provide valuable insights for policymakers, offering a framework to strengthen educational institutions in Pakistan. By integrating Islamic principles with contemporary practices, this research aims to promote an inclusive, equitable, and high-quality education system.